Formalin‐fixed paraffin‐embedded tissue: The holy grail of clinical proteomics. Issue 9 (October 2014) - Broeckx, Valérie; Peeters, Lise; Maes, Evelyne; Pringels, Lentel; Verjans, Eddy‐Tim; Landuyt, Bart; Bendixen, E.
<x xml:space="preserve">Abstract</x> Tissue is the most relevant biological material to gather insight in disease mechanisms by means of omics technologies. However, fresh frozen tissue, which is generally regarded as the best imaginable source for such studies, is often not available. In case it is available, the different ways of storage (e.g. −20°C, −80°C, liquid nitrogen, etc.) hamper the conduction of reproducible multicenter studies because of different protein degradation rates. Formalin‐fixed paraffin‐embedded (FFPE) tissue on the contrary is considered as a valuable alternative for fresh frozen tissue, because only a few standard operation procedures are applied worldwide for the preparation of these tissues and because they are all stored in the same way. However, a study on the impact of the different preparation protocols for FFPE tissue was still lacking. Therefore, Bronsert et al. in this issue [Bronsert, P., Weißer, J., Biniossek, M. L., Kuehs, M. et al., Proteomics Clin. Appl. 2014, 8 786–804] conducted such a study that provides proof that there is no significant effect between these sample preparations procedures, and thereby they further open the gate for FFPE tissues to enter the field of clinical proteomics.